High-throughput and energy-efficient Contiki MAC layer scheme in IEEE 802.15.4 for structural health monitoring - Al-Mekhlafi, Mohamed Abdulkarem Taher (2021)
The importance of wireless sensor networks (WSNs) in structural health monitoring (SHM) is unceasingly growing because of the increasing demand for both safety and security in the cities. WSN–based SHM system introduces a promising technology with compelling advantages compared to a traditional wired system. Nevertheless, the requirements of WSN-based SHM add extra complications and challenges to network design and the existing limitations of WSN technology. Some of these challenges result from the transmission of huge amounts of data in each data sensing period and the complexity of SHM algorithms. Furthermore, in WSNs, the operating system (OS) with its network protocol stack and media access control (MAC) layer protocol play an essential role in managing the scarce resources, data processing and communication. Nonetheless, in Contiki OS, there are constraints found in the actual version of Contiki that hinder its broader development, both in general and at the specific level of the network stack. Furthermore, there are constraints in implementing the provided Contiki carrier sense multiple access/collision avoidance (CSMA/CA) protocol. These constraints limit the available bandwidth by delaying data delivery and limiting the node's transmission capability along with high-power consumption. There is a research gap in developing a Contiki MAC layer scheme able to provide high throughput and secure an efficient utilization of the radio, which is inevitably the most critical part regarding power consumption in WSN for SHM. This motivates us to develop and implement a lightweight time division multiple access (L-TDMA) scheme to overcome the existing constraints on the networking stack’s implementation of MAC layer on Contiki and satisfy SHM requirements. The proposed concept is integrated with the Contiki architecture and tested experimentally and using the Cooja simulator. Besides, the design concept of the frame structure, slot distribution, scheduling and all associated calculations are illustrated. A synchronization model is presented with the aid of the implemented Contiki's implicit network time synchronization scheme. Finally, a case study of a WSN-based SHM system using developed embedded data filtering and transmission algorithms to reduce data communication is performed and taken place on a concrete beam at Civil Engineering Structure Laboratory, UPM. Simulation and experiments are performed to validate the design concept of LTDMA scheme and evaluate the sensor node's throughput, power consumption and the efficiency of the proposed embedded algorithms for SHM applications. The maximum number of packets that can be transmitted per second using L-TDMA are 137 packets (throughput of 139 kbps). In contrast, the default Contiki CSMA and TSCH can transmit at a maximum of 8 and 67 packets per second, respectively. The overall average channel throughput that can be provided by Contiki using L-TDMA is approximately 180 kbps at maximum. L-TDMA shows a significant reduction in power consumption compared to the default CSMA/CA, which achieves lower power consumption than CSMA/CA by 73% and 71% using simulation and testbed, respectively. Likewise, L-TDMA has lower power consumption by 9% than TSCH at an offered load of 8 pps. L-TDMA shows a remarkable ability to conserve power in comparison to other protocols in different operating systems. Finally, the implementation of the developed embedded algorithms for strain-based applications resulted in a power consumption reduction of 77% compared to centralized processing.